2010
DOI: 10.1002/app.32207
|View full text |Cite
|
Sign up to set email alerts
|

Influence of grafting on structural and optical properties of nylon‐6 fibers

Abstract: This study throws light on the change of the optical properties and some structural properties due to graft copolymerization of polydiallyldimethyl ammonium chloride (PDADMAC) and polyacrylamide (PAA) of nylon-6 fibers. Multiple-beam interferometric technique in transmission was used to study the change of the diameter, refractive indices, and birefringence of nylon-6 fibers at different graft yields. The results were utilized to investigate the isotropic refractive index, the mean polarizabilities per unit vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Results from microscopic photographs indicated that the fibers retained their morphology and shape well during the modification reactions though their diameters were greatly increased. The increased diameter was suggested to be due to the contribution of the grafted side chains 24, 25…”
Section: Resultsmentioning
confidence: 99%
“…Results from microscopic photographs indicated that the fibers retained their morphology and shape well during the modification reactions though their diameters were greatly increased. The increased diameter was suggested to be due to the contribution of the grafted side chains 24, 25…”
Section: Resultsmentioning
confidence: 99%
“…Hamza, Sokkar, El Farahaty, and El Dessouky () designed a heating device connected to a wedge interferometer and studied the influence of temperature on the optical and structure properties along the diameter of undrawn PP fibers. Seisa () studied, interferometrically, the influence of grafting rate on the change of diameter, refractive indices, and birefringence of nylon 6 fibers.…”
Section: Introductionmentioning
confidence: 99%
“…He determined the influence of the grafting degree on the moisture sorption, the swelling, and apparent activation energy of the modified fibers. Seisa investigated the change of optical properties and some structural properties of the nylon‐6 fibers due to graft copolymerization of polydiallyldimethyl ammonium chloride (PDADMAC) and polyacrylamide (PAA). The results reflected the suitable effect on the optical and structural properties of the grafted nylon‐6 fibers.…”
Section: Introductionmentioning
confidence: 99%